Syntheses, Spectroscopic, Electrochemical, and Third-Order Nonlinear Optical Studies of a Hybrid Tris{ruthenium(alkynyl)/(2-phenylpyridine)}iridium Complex - Zhao, H.; Simpson, Peter; Barlow, A.; Moxey, G.; Morshedi, M.; Roy, N.; Philip, R.; Zhang, C.; Cifuentes, M.; Humphrey, M. (2015)
The synthesis of fac-[Ir{N,C1′-(2,2′-NC5H4C6H3-5′-C C-1-C6H2-3,5-Et2-4-C CC6H4-4-C CH)}3] (10), which bears pendant ethynyl groups, and its reaction with [RuCl(dppe)2]PF6 to afford the heterobimetallic complex fac-[Ir{N,C1′-(2,2′-NC5H4C6H3-5′-C C-1-C6H2-3,5-Et2-4-C CC6H4-4-C C-trans-[RuCl(dppe)2])}3] (11) is described. Complex 10 is available from the two-step formation of iodo-functionalized fac-tris[2-(4-iodophenyl)pyridine]iridium(III) (6), followed by ligand-centered palladium-catalyzed coupling and desilylation reactions. Structural studies of tetrakis[2-(4-iodophenyl)pyridine-N,C1′](μ-dichloro)diiridium 5, 6, fac-[Ir{N,C1′-(2,2′-NC5H4C6H3-5′-C C-1-C6H2-3,5-Et2-4-C CH)}3] (8), and 10 confirm ligand-centered derivatization of the tris(2-phenylpyridine)iridium unit.Electrochemical studies reveal two (5) or one (6–10) Ir-centered oxidations for which the potential is sensitive to functionalization at the phenylpyridine groups but relatively insensitive to more remote derivatization. Compound 11 undergoes sequential Ru-centered and Ir-centered oxidation, with the potential of the latter significantly more positive than that of Ir(N,C′-NC5H4-2-C6H4-2)3. Ligand-centered π–π* transitions characteristic of the Ir(N,C′-NC5H4-2-C6H4-2)3 unit red-shift and gain in intensity following the iodo and alkynyl incorporation. Spectroelectrochemical studies of 6, 7, 9, and 11 reveal the appearance in each case of new low-energy LMCT bands following formal IrIII/IV oxidation preceded, in the case of 11, by the appearance of a low-energy LMCT band associated with the formal RuII/III oxidation process. Emission maxima of 6–10 reveal a red-shift upon alkynyl group introduction and arylalkynyl π-system lengthening; this process is quenched upon incorporation of the ligated ruthenium moiety on proceeding to 11. Third-order nonlinear optical studies of 11 were undertaken at the benchmark wavelengths of 800 nm (fs pulses) and 532 nm (ns pulses), the results from the former suggesting a dominant contribution from two-photon absorption, and results from the latter being consistent with primarily excited-state absorption.